1989
DOI: 10.1002/jbt.2570040102
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered V79 chinese hamster cell expression of purified cytochrome P‐450iib1 monooxygenase activity

Abstract: Chinese hamster V79 fibroblasts, frequently used as target cells in short-term tests for mutagenicity, do not possess measurable monooxygenase activity; in particular, enzymatic oxidation of testosterone (T) cannot be demonstrated. If these V79 cells, however, had been transfected with the cDNA-encoding rat liver cytochrome P-450IIB1 under control of the SV40 early promoter, they stably expressed monooxygenase activity. These so-called SD1 cells then oxidatively metabolized T at a rate of 27 pmol/mg protein/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…2). Both dioxane treatments induced several fold (about 18-20) 2B1/2-dependent 16b-testosterone hydroxylase, but only the acute dioxane administration was able to induce, although weakly, CYP3A-linked 6b-testosterone hydroxylase (Platt et al 1989), in keeping with the ErD data shown in Table 1. In addition, to our surprise, it was also observed that both 1,4-dioxane treatments induced 17OT-, 16a-and particularly 2a-testosterone hydroxylases linked to CYP2C11 (Platt et al 1989), the major P450 isoform constitutively present in the liver (Fujita et al 1989).…”
Section: Effects Of Dioxane Administration On Hepatic P450 Activitiessupporting
confidence: 82%
See 2 more Smart Citations
“…2). Both dioxane treatments induced several fold (about 18-20) 2B1/2-dependent 16b-testosterone hydroxylase, but only the acute dioxane administration was able to induce, although weakly, CYP3A-linked 6b-testosterone hydroxylase (Platt et al 1989), in keeping with the ErD data shown in Table 1. In addition, to our surprise, it was also observed that both 1,4-dioxane treatments induced 17OT-, 16a-and particularly 2a-testosterone hydroxylases linked to CYP2C11 (Platt et al 1989), the major P450 isoform constitutively present in the liver (Fujita et al 1989).…”
Section: Effects Of Dioxane Administration On Hepatic P450 Activitiessupporting
confidence: 82%
“…With both treatment regimens, strong and quite similar increases of CYP2B1/ 2-linked PROD and 2E1-linked p-NPH activities were observed in the liver. However, these treatments were not equivalent since dioxane administration by gavage but not that by drinking water also induced CYP3A-dependent activities such as ErD and 6b-testosterone hydroxylase (Arlotto et al 1987;Platt et al 1989). The induction of 2B1/2 in the liver following both acute and chronic dioxane treatment was also confirmed by marked enhancement of 16b-testosterone hydroxylase, a marker activity for this isoform (Platt et al 1989).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Testosterone hydroxylase was assayed as reported previously according to an HPLC method described by Platt et al [26], as previously reported [27]. Testosterone metabolites were resolved in a C18 RP Supelco column (250 × 4.6 mm) using an isocratic elution with methanol plus tetrahydrofuran (THF) 7.5% and H 2 O + THF 7.5% (27:73 v/v) for 8 min followed by a linear gradient reaching 42:58 v/v for 12 min and a final period of isocratic elution for further 10 min.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The concentration of metabolites was determined by the ratio between respective metabolite and corticosterone (internal standard) peak areas, and the calibration curves obtained with synthetic testosterone derivatives. 40,41 The associated CYP isoforms are: 6␣ (CYP2A1, CYP2B1), 6␤ (CYP3A), and 16␣ (CYP2B9). 42 …”
Section: Testosterone Hydroxylase Activitymentioning
confidence: 99%